Generation Z Performance Management: Challenges And Opportunities In Public Sector Organizations - Pratama, Rafly Andika; Fadillah, Bayu; Fadhila, Irfan (Syntax Literate, 2025)
Demographic shifts in the workplace have positioned Generation Z as key actors in modern organizations. This cohort is characterized by high technological adaptability, a strong preference for work flexibility, and a desire for work-life balance within inclusive environments. This study explores the opportunities and challenges in managing Generation Z's performance in organizational settings. Employing a literature review, the findings indicate that while Generation Z fosters innovation and drives digital transformation, they also present challenges related to rigid job structures and a reduced propensity for long-term commitment. Organizations must adapt by cultivating flexibility and promoting cross-sector collaboration. With appropriate strategies, Generation Z’s potential can be optimized to support sustainable organizational performance.